CHANGES IN THE INCOMES AND EXPENDITURES OF HOUSEHOLDS IN POLAND AND THEIR REGIONAL RELATIONS - Beata Kasprzyk; Małgorzata Leszczyńska (Polityki Europejskie, Finanse i Marketing)
The article assesses the financial situation of households in 2000-2019 in prospect of changes of incomes and expenditures in Poland. It has been assumed, as a point of reference, that dispersionof the analysed processes is dependent on geographical area– therefore regional scale was applied. To the analysis and comparison the data from the researches on households budgetsperformed by GUS were used. Adopting simultaneously an econometric approach (considering the time (years 2000-2019) as independent, explanatory variable) analytical trend functions wereestimated. A retrospective analysis of the incomes and expenditures of the population of Poland indicates the growing trends. Regional comparative analysis of households allows to drawconclusions that level of economic condition is very diversified.